Disease Flare and Reactogenicity in Patients With Rheumatic and Musculoskeletal Diseases Following Two‐Dose SARS–CoV‐2 Messenger RNA Vaccination. Issue 1 (3rd December 2021) - Connolly, Caoilfhionn M.; Ruddy, Jake A.; Boyarsky, Brian J.; Barbur, Iulia; Werbel, William A.; Geetha, Duvuru; Garonzik‐Wang, Jacqueline M.; Segev, Dorry L.; Christopher‐Stine, Lisa; Paik, Julie J.
Abstract : Objective: To evaluate disease flare and postvaccination reactions (reactogenicity) in patients with rheumatic and musculoskeletal diseases (RMDs) following 2‐dose SARS–CoV‐2 messenger RNA (mRNA) vaccination. Methods: RMD patients (n = 1, 377) who received 2‐dose SARS–CoV‐2 mRNA vaccination between December 16, 2020 and April 15, 2021 completed questionnaires detailing local and systemic reactions experienced within 7 days of each vaccine dose (dose 1 and dose 2), and 1 month after dose 2, detailing any flares of RMD. Associations between demographic/clinical characteristics and flares requiring treatment were evaluated using modified Poisson regression. Results: Among the patients, 11% reported flares requiring treatment; there were no reports of severe flares. Flares were associated with prior SARS–CoV‐2 infection (incidence rate ratio [IRR] 2.09, P  = 0.02), flares in the 6 months preceding vaccination (IRR 2.36, P  < 0.001), and the use of combination immunomodulatory therapy (IRR 1.95, P  < 0.001). The most frequently reported local and systemic reactions included injection site pain (87% after dose 1, 86% after dose 2) and fatigue (60% after dose 1, 80% after dose 2). Reactogenicity increased after dose 2, particularly for systemic reactions. No allergic reactions or SARS–CoV‐2 diagnoses were reported. Conclusion: Flares of underlying RMD following SARS–CoV‐2 vaccination were uncommon. There were no reports of severe flares. Local and systemic reactions typically did not interfere with daily activity. These early safety data can help address vaccine hesitancy in RMD patients.